BIOLOGY TEACHERS' TPACK SELF-EFFICACY IN PRACTICAL WORK DURING DISTANCE LEARNING - Muthmainnah, Rifaatul; Nurkamilah, Siti (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to explore Biology teachers' TPACK self-efficacy on practical work during distance learning. The descriptive method was used with 42 participants who joined as Biology teacher association in Garut city, determined by random sampling. The data were collected through an online self-assessment questionnaire to explore teachers' perceived self-efficacy. Data analysis is done descriptively. The results showed that biology teachers have a good self-efficacy on their TPACK. Biology teachers are confident that they will carry out practical work successfully during this pandemic crisis. Biology teachers tend to show better self-efficacy in content knowledge than knowledge related to technology. However, they generally still show enthusiasm to increase their technological knowledge. The results indicate sustained integration of technology in learning even after the COVID-19 crisis, for example, when blended learning is in the future. This research may be used to develop a professional program to improve teachers' TPACK. Abstrak: Penelitian ini bertujuan untuk mengeksplorasi self-efficacy guru Biologi terhadap TPACK pada kegiatan praktikum selama pembelajaran jarak jauh. Metode deskriptif digunakan dalam penelitian ini dengan melibatkan 42 guru yang tergabung sebagai anggota musyawarah guru mata pelajaran Biologi di Kota Garut dan dipilih secara acak. Data dikumpulkan melalui kuesioner penilaian diri untuk mengeksplorasi self-efficacy yang dimiliki guru. Analisis data dilakukan secara deskriptif. Hasil penelitian menunjukkan bahwa guru Biologi memiliki self-efficacy yang baik pada TPACK mereka. Guru Biologi percaya diri bahwa mereka bisa melaksanakan kegiatan praktikum dengan sukses selama pandemi COVID-19. Guru Biologi cenderung menunjukkan self-efficacy yang lebih baik dalam hal pengetahuan konten, jika dibandingkan dengan pengetahuan yang berkaitan dengan teknologi. Tetapi umumnya tetap menunjukkan antusias untuk meningkatkan pengetahuan teknologinya. Hasil penelitian ini mengindikasikan potensi integrasi teknologi yang berkelanjutan dalam praktikum berbasis online terutama ketika blended learning menjadi keharusan setelah melewati masa krisis pandemi COVID-19. Hasil penelitian ini dapat dijadikan dasar untuk mengembangkan program profesionalisme guru dalam meningkatkan kemampuan TPACK.